PROSES KERJA SAMA PT BIO FARMA DAN SINOVAC BIOTECH LTD MELALUI DIPLOMASI MULTI JALUR PERIODE TAHUN 2020-2022 - Sellin Alicia Anjani (2024)
Since the beginning of 2020, the Covid-19 pandemic has become a global threat. Every country is making various collaborative efforts to be able to overcome the problem of the Covid-19 pandemic. During this pandemic, Indonesia has become one of the countries that is active in building cooperative relationships. This was proven when Indonesia implemented its vaccine diplomacy strategy. Vaccine diplomacy is a cooperative strategy carried out by Indonesia during the Covid-19 pandemic. In its implementation, vaccine diplomacy is carried out in a multi-track way where the state is no longer the main actor. The vaccine diplomacy carried out certainly has various objectives. Apart from securing ample vaccine availability, this strategy has the aim of fighting for fair and equitable access to health. So, there is no longer a potential gap between countries in seeing the problem of the Covid-19 pandemic. This research uses a descriptive qualitative method that looks at the cooperation process between PT Bio Farma and Sinovac Biotech Ltd through multi-track diplomacy for the 2020-2022 period. This research shows that, through its vaccine diplomacy strategy, Indonesia has succeeded in building international cooperation and successfully carrying out technology transfers and of course this has shown significant results. Keywords: Covid-19, Vaccine diplomacy, Indonesia, Technology transfer